Desulfurization of Vulcanized Rubber Particles Using Biological and Couple Microwave-Chemical Methods - Valdés, C.; Hernández, C.; Morales-Vera, R.; Andler, R. (Frontiers in Environmental Science, 2021)
Currently, recycling or degradation treatments for tires are an enormous challenge. Despite efforts to dispose of or recycle it, rubber waste is increasing year by year worldwide. To create a rubber-recycling system, several researchers have proposed tire desulfurization. In this study, we compare two methods: one biological, using Acidobacillus ferroxidans in shake 250 mL flask experiments, and one chemical using, for the first time, microwaves and an aqueous solution. The results of these methods were analyzed through sulfate quantification, cross-linking differences, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy with energy disperse spectroscopy (SEM-EDS). We observed that the amount of sulfates generated by the chemical system was 22.40 (mg/L)/g of rubber, which was 22-times higher than the biological system, which generated 1.06 (mg/L)/g of rubber. Similarly, after cross-linking studies, a 36% higher decrease after the chemical treatment was observed. When using FTIR analysis, the disappearance of characteristic bands corresponding to functional groups containing sulfur bonds was observed by treating the sample with both desulfurization mechanisms. Morphological changes on the rubber surface structure was also demonstrated by SEM-EDS analysis with the appearance of holes, cracks and changes in the porosity of the material. This work analyzed two different non-aggressive desulfurization mechanisms that might be used as sustainable methods for rubber recycling processes.